The Genesis of Advertising Communication in the Republic of Belarus: The Ontological Status - Solodovnikova, Tatiana (Philology & Human, 2021)
The paper presents the research based on the Belarus’s archival materials to trace the genesis of advertising communication starting from the 10th century to present-day Republic of Belarus. The work reveals that the formation and development of advertising communication evolved on the basis of European-wide traditions, but had a number of specific peculiarities. If the technological factor prevails to the forms of advertising communication and ways to reach the target audience, the social political factor has predetermined the content and role of advertising in modern Belarusian society: in the absence of a sovereign state and profound territorial fragmentation, advertising activities in Belarus appeared as a result of the manufacturers’ needs to promote their goods and services. The specifics of advertising communication in the Republic of Belarus are manifested in the slower rate of development progress in comparison to the European level and in the high sensitivity to the political context.